LB2. Safety and Efficacy of Combination SARS-CoV-2 Monoclonal Neutralizing Antibodies (mAb) BRII-196 and BRII-198 in Non-Hospitalized COVID-19 Patients. (4th December 2021) - Evering, Teresa H; Giganti, Mark; Chew, Kara W; Hughes, Michael; Moser, Carlee; Wohl, David Alain; Currier, Judith; Eron, Joseph J; Javan, Arzhang; Margolis, David A; Zhu, Qing; D'Andrea, Ulises; et al.
Abstract: Background: SARS-CoV-2 continues to spread and the development of safe and effective therapeutics for the prevention of severe disease remains a priority. BRII-196 and BRII-198 are non-competing anti-SARS-CoV-2 mAbs with YTE triple amino acid substitution in Fc to extend half-life and reduce receptor binding, that are being studied for treatment of COVID-19 in the ACTIV-2 Trial, sponsored by NIAID and led by ACTG. Methods: ACTIV-2 evaluates safety/efficacy of investigational agents for treatment of non-hospitalized adults with mild-moderate COVID-19 under a randomized, blinded, controlled adaptive platform. BRII-196/BRII-198 (1000 mg each) as a single dose given as sequential infusions, or placebo to those at high risk of clinical progression (i.e., age ≥ 60 years or presence of other medical conditions) within 10 days of symptom onset and positive test for SARS-CoV-2. The primary endpoint was hospitalization and/or death through day 28. We report Phase 3 BRII-196/BRII-198 trial results per DSMB recommendation following an interim analysis. Results: Between January and July 2021, 837 participants (418 active, 419 placebo) from sites in the US (66%), Brazil, South Africa, Mexico, Argentina and the Philippines were randomized and received study product at time of emerging variants. Median age 49 years (Q1, Q3: 39, 58), 51% female, 17% Black/African-American and 49% Hispanic/Latino, with median 6 days from symptom onset. At interim analysis 71% and 97% had a day 28 and 7 visit, respectively. For all available data at interim review, BRII-196/BRII-198 compared to placebo had fewer hospitalizations (12 vs. 45) and deaths (1 vs. 9). At day 28 of follow-up, there was an estimated 78% reduction in hospitalization and/or death (2.4 vs. 11.1%), relative risk 0.22 (95% CI: 0.05, 0.86), P=0.00001 (nominal one-sided). Grade 3 or higher adverse events (AEs) were observed less frequently among BRII-196/BRII-198 participants than placebo (3.8% vs. 13.4%) with no severe infusion reactions or drug related serious AEs. Conclusion: BRII-196/BRII-198 was safe, well-tolerated, and demonstrated significant reduction compared to placebo in the risk of hospitalization and/or death among adults with mild-moderate COVID-19 at high risk for progression to severe disease. Disclosures: Kara W. Chew, MD, MS, Amgen (Individual(s) Involved: Self): Grant/Research Support; Merck Sharp & Dohme (Individual(s) Involved: Self): Grant/Research Support David Alain Wohl, MD, Gilead Sciences (Individual(s) Involved: Self): Advisor or Review Panel member, Consultant, Research Grant or Support, Scientific Research Study Investigator; Janssen (Individual(s) Involved: Self): Advisor or Review Panel member; Merck (Individual(s) Involved: Self): Advisor or Review Panel member, Research Grant or Support; ViiV (Individual(s) Involved: Self): Advisor or Review Panel member, Research Grant or Support Joseph J. Eron, MD, Gilead Sciences (Consultant, Research Grant or Support)Janssen (Consultant, Research Grant or Support)Merck (Consultant)ViiV (Consultant, Research Grant or Support) David A. Margolis, MD MPH, Brii Biosciences (Employee) Courtney Fletcher, Pharm.D., National Institute of Allergy and Infectious Diseases, NIH (Grant/Research Support) Davey Smith, M.D., Linear Therapies, Matrix Biomed, Bayer (Consultant, Shareholder) Eric Daar, Gilead (Consultant, Grant/Research Support)Merck (Consultant)ViiV (Consultant, Grant/Research Support)